Chitosan-based iron-copper co-doped carbon material as well as preparation method and application thereof
By employing glutamic acid to form chitosan-based hydrogel, the method achieves uniform distribution of Fe and Cu nanoclusters, enhancing the catalytic performance of carbon materials, addressing the limitations of existing carbon-based catalysts and achieving superior oxygen reduction activity.
Patent Information
- Application Number
- CN202411242680.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-13
AI Technical Summary
Carbon-based catalysts exhibit inferior catalytic activity compared to precious metal-based catalysts, and existing methods for modifying carbon materials with transition metals like iron and copper face challenges in uniform distribution and toxicity issues.
A method involving the use of acidic amino acids, specifically glutamic acid, to form chitosan-based hydrogel without toxic cross-linking agents, facilitating controlled distribution of Fe and Cu nanocrystals in carbon materials, forming uniformly dispersed nanoclusters with enhanced porosity and active sites.
The resulting chitosan-based iron-copper co-doped carbon material demonstrates improved electrocatalytic performance, with higher half-wave potential and oxygen reduction reaction activity, surpassing commercial platinum carbon materials.
Smart Images

Figure CN119114077A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon-based catalysts, and specifically relates to a chitosan-based iron-copper co-doped carbon material and a preparation method and application thereof. Background Art
[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] Carbon nanomaterials are often used as electrode catalysts in fuel cells, metal-air batteries, water electrolysis and other devices due to their advantages such as high conductivity, high specific surface area and strong tolerance. However, a large number of research results show that although pure carbon-based catalysts have certain electrocatalytic activity, their catalytic activity is still far inferior to that of commercial precious metal-based catalysts and cannot meet practical needs.
[0004] In order to improve the catalytic activity of carbon-based catalysts, it is necessary to modify their structure. At present, coupling carbon nanomaterials with other active components (metals and non-metals) to form a hybrid system is a common method for modifying carbon-based catalysts. The hybridized carbon-based catalyst will produce new active sites, change the adsorption strength of the catalyst surface to the reaction intermediates, and thus improve the electrocatalytic performance of the carbon-based catalyst.
[0005] Transition metals such as iron and copper have the advantages of abundant reserves on earth, low cost, and high theoretical activity, and are widely used as doping modifications of carbon materials. However, the distribution pattern, particle size, and active site types of transition metals in carbon-based materials are regulated by the structure and type of carbon-based materials, and are closely related to the activity and reaction mechanism of transition metal-doped carbon material catalysts. Among them, three-dimensional porous carbon aerogel materials are the most popular in the field of electrocatalysis due to their high specific surface area, high porosity, large number of exposed active sites, good electrolyte diffusivity, and high structural stability, and are often used as carriers of metal carbon-based electrocatalysts.
[0006] Chitosan-based hydrogel is a biodegradable, biocompatible, inexpensive, and environmentally friendly material. The most important thing is that chitosan contains abundant amino (-NH2) and hydroxyl (-OH) groups. 3+ , Cu 2+ Strong chelation between ions and Fe 3+ , Cu 2+ The complexation of ions with the amino (-NH2) and hydroxyl (-OH) functional groups on the chitosan chain can help the distribution of transition metals in carbon materials to a certain extent, but the distribution state of Fe and Cu nanocrystals in carbon materials is still difficult to uniformly control.
[0007] At present, the main methods for gelation of chitosan include cross-linking polymerization, graft copolymerization, interpenetrating network method, etc. The most commonly used cross-linking agents are formaldehyde, N,N'-methylenebisacrylamide, glutaraldehyde, epichlorohydrin, etc. These cross-linking agents are mostly cytotoxic and easily cause secondary pollution. Summary of the invention
[0008] In view of the deficiencies in the prior art, the present invention aims to provide a chitosan-based iron-copper co-doped carbon material and a preparation method and application thereof.
[0009] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0010] In a first aspect, the present invention provides a method for preparing a chitosan-based iron-copper co-doped carbon material, comprising the following steps:
[0011] The mixed aqueous solution of glutamic acid and soluble iron salt is mixed with the mixed aqueous solution of chitosan and soluble copper salt to obtain a mixed solution, and the mixed solution is heated in a water bath and stirred for a set time to obtain an iron-copper ion co-doped chitosan-based hydrogel;
[0012] The iron-copper ion co-doped chitosan-based hydrogel is frozen and then freeze-dried to obtain the iron-copper ion co-doped chitosan-based aerogel;
[0013] The chitosan-based aerogel co-doped with iron and copper ions is calcined in an inert atmosphere to obtain a chitosan-based iron and copper co-doped carbon material.
[0014] In view of the fact that the gelation of chitosan usually requires the use of a cytotoxic crosslinking agent and the difficulty in controlling the distribution state of Fe and Cu nanocrystals in carbon materials, the present invention introduces acidic amino acids into the preparation process of chitosan gel, so that it can take into account the dual functions of acid regulator and structure directing agent, successfully obtain chitosan-based hydrogel, and does not introduce commonly used organic structure inducing agents with certain toxicity, so as not to cause secondary pollution. The abundant -NH2, -COOH and -OH functional groups in chitosan and glutamic acid react with Fe 3+ , Cu 2+ The interaction between Fe and Cu can effectively control the formation and dispersion of Fe and Cu nanocrystals in chitosan-based carbon materials, and chitosan-based carbon materials uniformly doped with Fe and Cu are obtained.
[0015] In some embodiments, the soluble iron salt is ferric nitrate, ferric sulfate, ferric chloride or ferrous chloride.
[0016] In some embodiments, the soluble copper salt is copper nitrate, copper sulfate, or copper chloride.
[0017] In some embodiments, in the mixed solution, the concentration of glutamic acid is 10-50 mg / mL; the concentration of soluble iron salt is 1-100 mg / mL; the concentration of chitosan is 15-75 mg / mL; and the concentration of soluble copper salt is 0.5-60 mg / mL.
[0018] Preferably, in the mixed solution, the concentration of glutamic acid is 20-40 mg / mL; the concentration of soluble iron salt is 10-80 mg / mL; the concentration of chitosan is 30-60 mg / mL; and the concentration of soluble copper salt is 10-50 mg / mL.
[0019] In some embodiments, the water bath heating temperature is 90-100° C., and the water bath heating time is 3-10 min.
[0020] Preferably, the water bath heating temperature is 92-97° C., and the water bath heating time is 3-7 min.
[0021] In some embodiments, the temperature for freezing the iron-copper ion co-doped chitosan-based hydrogel is -70 to -90°C, and the freezing time is 20 to 30 hours.
[0022] In some embodiments, the temperature for calcining the iron-copper ion co-doped chitosan-based aerogel is 800-1000° C., and the calcination time is 1-6 hours.
[0023] Preferably, during the calcination process, the heating rate is 8-10°C min -1 .
[0024] In a second aspect, the present invention provides a chitosan-based iron-copper co-doped carbon material prepared by the preparation method.
[0025] In a third aspect, the present invention provides use of the chitosan-based iron-copper co-doped carbon material in the preparation of an electrode catalyst.
[0026] The beneficial effects achieved by one or more embodiments of the present invention are as follows:
[0027] (1) Acidic glutamic acid induces chitosan to form hydrogel, without the need to use other toxic cross-linking agents, which is non-toxic and environmentally friendly.
[0028] (2) The abundant -NH2, -COOH and -OH functional groups in chitosan and glutamic acid react with Fe 3+ , Cu 2+ The interaction can effectively control the formation and dispersion of Fe and Cu nanoclusters in chitosan-based carbon materials, forming chitosan-based carbon materials with uniformly dispersed Fe and Cu nanoclusters, and the size of the nanoclusters is about 1 nm.
[0029] (3) In the present invention, the addition of iron salt can increase the porosity of chitosan-based carbon materials, thereby increasing the specific surface area of the catalyst, which is beneficial to improving the catalytic performance of the catalyst; the addition of copper salt can effectively reduce the size of metal nanoparticles, so that the size of the iron-copper nanoclusters of chitosan-based iron-copper co-doped carbon materials is about 1nm, and has bimetallic active sites, so it has a good interface microenvironment, which is beneficial to the adsorption and desorption of intermediates, thereby improving the electrocatalytic performance. The results show that the half-wave potential (0.94V) of the chitosan-based iron-copper co-doped carbon material catalyst in oxygen-saturated KOH solution (0.1M) is higher than the half-wave potential (0.89V) of the commercial platinum carbon material, indicating that the chitosan-based iron-copper co-doped carbon material has high oxygen reduction reaction activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0031] Figure 1 This is a transmission electron microscope morphology characterization image of the chitosan-based iron-copper co-doped carbon material prepared in Example 1 of the present invention;
[0032] Figure 2 It is a comparison diagram of linear sweep voltammetric curves of the chitosan-based iron-copper co-doped carbon material prepared in Example 1 of the present invention and the commercial platinum-carbon material in an oxygen-saturated potassium hydroxide solution (0.1 M);
[0033] Figure 3 This is a transmission electron microscope morphology characterization image of the chitosan-based carbon material prepared in Comparative Example 1 of the present invention;
[0034] Figure 4 This is a transmission electron microscope morphology characterization image of the chitosan-based carbon material prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0035] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0036] The present invention will be further described below in conjunction with the embodiments.
[0037] Example 1
[0038] 0.3 g of glutamic acid, 0.2 g of ferric nitrate nonahydrate, and 6.5 mL of water were placed in beaker A. Beaker A was heated in a 95°C constant temperature water bath until all the contents were dissolved. The dissolved solution was recorded as liquid A.
[0039] 0.5 g of chitosan, 0.2 g of copper nitrate trihydrate, and 4.0 mL of water were placed in beaker B and dispersed by magnetic stirring to form a suspension, which was recorded as liquid B.
[0040] Liquid B was poured into liquid A, and heated and stirred in a 95°C water bath for 5 minutes to finally prepare iron-copper ion co-doped chitosan-based hydrogel.
[0041] The iron-copper ion co-doped chitosan-based hydrogel was frozen in a -80°C low-temperature refrigerator for 24 hours, and then freeze-dried by a freeze dryer to remove the contained moisture, thereby obtaining the iron-copper ion co-doped chitosan-based aerogel.
[0042] The iron-copper ion co-doped chitosan-based aerogel was calcined in a tubular furnace at a temperature of 900 °C and a heating rate of 10 °C min -1 After calcination, the mixture was naturally cooled to room temperature to obtain chitosan-based iron-copper co-doped carbon material.
[0043] Figure 1 This is a transmission electron microscopy morphology characterization of chitosan-based iron-copper co-doped carbon material. The transmission electron microscopy image shows that the chitosan-based iron-copper co-doped carbon material presents a porous carbon structure without the presence of large-sized metal particles. It can be clearly observed that a large number of iron-copper nanoclusters with a size of about 1 nm are uniformly distributed in the prepared chitosan-based iron-copper co-doped carbon material.
[0044] Figure 2 This is a comparison of the linear sweep voltammetric curves of chitosan-based iron-copper co-doped carbon material and commercial platinum-carbon material in an oxygen-saturated potassium hydroxide solution (0.1M). The results show that the half-wave potential (0.94V) of the chitosan-based iron-copper co-doped carbon material catalyst in an oxygen-saturated KOH solution (0.1M) is higher than the half-wave potential (0.89V) of the commercial platinum-carbon material, indicating that the chitosan-based iron-copper co-doped carbon material has a high oxygen reduction reaction activity.
[0045] Example 2
[0046] 0.3 g of glutamic acid, 0.5 g of ferric nitrate nonahydrate, and 6 mL of water were measured and placed in beaker A. Beaker A was heated in a constant temperature water bath at 100°C until all the contents were dissolved. The dissolved solution was recorded as liquid A.
[0047] 0.5 g of chitosan, 0.3 g of copper nitrate trihydrate, and 4.0 mL of water were placed in beaker B and dispersed by magnetic stirring to form a suspension, which was recorded as liquid B.
[0048] Liquid B was poured into liquid A, and heated and stirred in a 95°C water bath for 5 minutes to finally prepare iron-copper ion co-doped chitosan-based hydrogel.
[0049] The iron-copper ion co-doped chitosan-based hydrogel was frozen in a -80°C low-temperature refrigerator for 24 hours, and then freeze-dried by a freeze dryer to remove the contained moisture, thereby obtaining the iron-copper ion co-doped chitosan-based aerogel.
[0050] The iron-copper ion co-doped chitosan-based aerogel was calcined in a tubular furnace at a temperature of 900 °C and a heating rate of 10 °C min -1 After calcination, the mixture was naturally cooled to room temperature to obtain chitosan-based iron-copper co-doped carbon material.
[0051] Example 3
[0052] 0.3 g of glutamic acid, 0.01 g of ferric nitrate nonahydrate, and 5.5 mL of water were placed in beaker A. Beaker A was heated in a 90°C constant temperature water bath until all the contents were dissolved. The dissolved solution was recorded as liquid A.
[0053] 0.4 g chitosan, 0.01 g copper nitrate trihydrate, and 3.5 mL water were placed in beaker B and dispersed by magnetic stirring to form a suspension, which was recorded as liquid B.
[0054] Liquid B was poured into liquid A, and heated and stirred in a 90°C water bath for 5 minutes to finally prepare iron-copper ion co-doped chitosan-based hydrogel.
[0055] The iron-copper ion co-doped chitosan-based hydrogel was frozen in a -80°C low-temperature refrigerator for 24 hours, and then freeze-dried by a freeze dryer to remove the contained moisture, thereby obtaining the iron-copper ion co-doped chitosan-based aerogel.
[0056] The iron-copper ion co-doped chitosan-based aerogel was calcined in a tubular furnace at a temperature of 900 °C and a heating rate of 10 °C min -1 After calcination, the mixture was naturally cooled to room temperature to obtain chitosan-based iron-copper co-doped carbon material.
[0057] Comparative Example 1
[0058] The difference from Example 1 is that ferric nitrate nonahydrate is omitted, and the rest is the same as Example 1. The specific surface area of the obtained chitosan-based copper-doped carbon material is reduced, so that the specific surface area of the catalyst is reduced from 289.1394 m 2 / g reduced to 182.7540m 2 / g, such as Figure 3 shown.
[0059] Comparative Example 2
[0060] The difference from Example 1 is that copper nitrate trihydrate is omitted, and the rest is the same as Example 1. The size of the obtained chitosan-based iron-doped carbon material metal nanoparticles increases to 20±10 nm, and the morphology is uneven, which reduces the active sites of the catalyst, such as Figure 4 shown.
[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a chitosan-based iron-copper co-doped carbon material, characterized in that: The steps include: The mixed aqueous solution of glutamic acid and soluble iron salt is mixed with the mixed aqueous solution of chitosan and soluble copper salt to obtain a mixed solution, and the mixed solution is heated in a water bath and stirred for a set time to obtain an iron-copper ion co-doped chitosan-based hydrogel; The iron-copper ion co-doped chitosan-based hydrogel is frozen and then freeze-dried to obtain the iron-copper ion co-doped chitosan-based aerogel; The chitosan-based aerogel co-doped with iron and copper ions is calcined in an inert atmosphere to obtain a chitosan-based iron and copper co-doped carbon material.
2. The method for preparing chitosan-based iron-copper co-doped carbon material according to claim 1, characterized in that: The soluble iron salt is ferric nitrate, ferric nitrate, ferric sulfate, ferric chloride or ferrous chloride.
3. The method for preparing chitosan-based iron-copper co-doped carbon material according to claim 1, characterized in that: The soluble copper salt is copper nitrate, copper sulfate or copper chloride.
4. The method for preparing chitosan-based iron-copper co-doped carbon material according to claim 1, characterized in that: In the mixed solution, the concentration of glutamic acid is 10-50 mg / mL; the concentration of soluble iron salt is 1-100 mg / mL; the concentration of chitosan is 15-75 mg / mL; and the concentration of soluble copper salt is 0.5-60 mg / mL.
5. The method for preparing chitosan-based iron-copper co-doped carbon material according to claim 1, characterized in that: The water bath heating temperature is 90-100°C, and the water bath heating time is 3-10 minutes.
6. The method for preparing chitosan-based iron-copper co-doped carbon material according to claim 5, characterized in that: The water bath heating temperature is 92-97°C, and the water bath heating time is 3-7 minutes.
7. The method for preparing chitosan-based iron-copper co-doped carbon material according to claim 1, characterized in that: The temperature for freezing the iron-copper ion co-doped chitosan-based hydrogel is -70 to -90°C, and the freezing time is 20 to 30 hours.
8. The method for preparing chitosan-based iron-copper co-doped carbon material according to claim 1, characterized in that: The iron-copper ion co-doped chitosan-based aerogel is calcined at a temperature of 800-1000° C. for a calcination time of 1-6 h; Preferably, during the calcination process, the heating rate is 8-10°C min -1 .
9. A chitosan-based iron-copper co-doped carbon material, characterized in that: Prepared by the preparation method described in any one of claims 1 to 8.
10. Use of the chitosan-based iron-copper co-doped carbon material according to claim 9 in the preparation of electrode catalysts.
